Wheat-associated Pseudomonas taiwanensis WRS8 reduces cadmium uptake by increasing root surface cadmium adsorption and decreasing cadmium uptake and transport related gene expression in wheat. (1st January 2021) - Cheng, Cheng; Wang, Qi; Wang, Qing-Xiang; He, Lin-Yan; Sheng, Xia-Fang
Abstract: Metal-resistant bacteria can reduce Cd accumulation in plants, but mechanisms underlying this effect are poorly understood. In this study, a highly effective Cd-resistant WRS8 strain was obtained from the rhizoshere soil of Triticum aestivum L . Yangmai-13 and identified as Pseudomonas taiwanensis based on 16S rRNA gene sequence analysis. Strain WRS8 was investigated for its effects on Cd availability and wheat tissue Cd contents and the related mechanisms using a hydroponic culture experiment. In strain WRS8-inoculated solution, the Cd concentration reduced and the pH and cell-adsorbed Cd increased with time. Strain WRS8 increased the wheat root and above-ground tissue dry weights by 11–36% compared to the controls. In strain WRS8-inoculated wheat plants, the Cd contents of the roots and above-ground tissues decreased by 78–85% and 88–94% and the Cd bioconcentration and translocation factors decreased by 78–85% and 46–58% at days 3 and 10, respectively, compared with the controls. The root surface-adsorbed Cd contents increased by 99–121% in the WRS8 strain-inoculated wheat plants at days 3 and 10 compared to the controls. Furthermore, strain WRS8 colonized the wheat root surfaces and interiors and reduced the expression levels of the LCT1 and HMA2 genes involved in Cd accumulation and transport in wheat roots by 46% and 30%, respectively, compared to the controls. In the Cd-contaminated soils, strain WRS8 significantly reduced the available Cd content by 20–24% and increased the pH compared to the controls. These findings showed the important role of strain WRS8 in reducing solution and soil Cd availability and suggested that strain WRS8 reduced the wheat tissue Cd accumulation by increasing root surface Cd adsorption and decreasing wheat root Cd uptake and transport-related gene expression and may provide a new and effective wheat rhizobacteria-enhanced approach for reducing wheat Cd uptake in Cd-polluted environments. Graphical abstract: Image 1 Highlights: Cd-resistant Pseudomonas taiwanensis WRS8 was obtained from wheat rhizosphere soil. WRS8 immobilized solution Cd by increasing pH and cell and floccules adsorption. WRS8 significantly increased the biomass and reduced Cd uptake of wheat seedlings. WRS8 increased wheat root surface-adsorbed Cd and reduced Cd translocation. WRS8 reduced expression of Cd uptake and transport-related genes in wheat roots. Abstract : Strain WRS8 decreased wheat tissue Cd uptake through increasing root surface Cd adsorption and decreasing root Cd accumulation and transport-related gene expression levels.